Solidification characteristics of atomized AlCu4Mg1-SiC composite powders - Yamanoglu R.; Zeren M.; German Randall M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study, rapidly solidified metal matrix composite powders have been produced by PREP (Plasma rotating electrode process) atomization. AlCu4Mg1 alloy is used as the matrix material while SiC particles, with about 650 nm average particle size, are used as the reinforcement phase. The microstructural and solidification characteristics of composite particles are studied using optical and scanning electron microscope (SEM). The relationship between secondary dendrite arm spacing (SDAS) and particle diameter was examined, and these composite powders were found to have dendritic and equiaxed solidification with a fine eutectic phase. SDAS measurements using various sized particles show that secondary dendrite arm spacing slightly decreases with the decrease in particle size.